GENERALIZED STAR MODELING WITH HETEROSKEDASTIC EFFECT - Wulandari, Kesi
One alternative to reduce congestion in Bandung is by using the toll road. However, there is an increase in the number of vehicles entering and also exiting toll road. Therefore, other alternative is needed to reduce congestion. In determining other alternative, it is necessary to estimate the number of vehicles entering and exiting the toll road. The space-time model is used to estimate the number of vehicles for short time. But, space-time model has assumptions that must be approved in its use. That assumptions such as errors is obtained independent and variances of error are constant with time. However, variances of error are not constant with time or there is heteroskedastic effect. Because of that, space-time model with heteroskedastic effect is applied in estimating number of vehicles in finding other alternative.